The Correlation between Family Conflict and Aggression Symptoms in High School Students - Nela V. Marinković; Ivana T. Zečević (University of Belgrade, Teacher Education Faculty, 2019)
The goal of this paper is to examine whether family conflicts can predict aggression symptoms in adolescents and to provide guidance for intervention and prevention. The research was conducted on a sample of 1036 respondents/high school students (grades 1-4) from Banja Luka and Čelinac (Bosnia and Herzegovina). The 61.3% of the respondents were female. Instruments for assessing the family climate experience were used in the research, the Family Conflict subscale (FCI - Family Climate Inventory; Mihić et al. 2006), as well as the Questionnare for Assessing Agression Symptoms - BODTH (Dinić et al., 2014). The research tested the hypothesis that family conflicts can predit aggression in adolescents. The findings confirmed the hypothesis that family conflict is a statistically significant prediction method for: anger ((F (1,1034)=73,81, p<0.000; R2=0.067), vindictiveness (F (1,1034)=24,18, p<0.000; R2=0.023), domination (F (1,1034)=63,55, p<0.000; R2=0.058) and hostility (F (1,1034)=49,94, p<0.000; R2=0.046). The obtained results were discussed in relation to the importance of information in a family and educational context, with implications for intervention and prevention.